Documentary Resources of the Institute of the Presidency in the Republic of Kazakhstan: Forms of Preservation and Provision of Access - Udovуk Volodymyr (Наукові праці Національної бібліотеки України імені В.І. Вернадського, 2022)

(untitled)
The article examines the forms of organizing the formation and preservation of the documentary heritage of the Institute of the Presidency of the Republic of Kazakhstan, in particular the Library of the First President of the Republic of Kazakhstan - Elbasy, the Museum of the Library of the First President of the Republic of Kazakhstan, the Archive of the President of the Republic of Kazakhstan, etc. Documentary resources of the institution of the presidency in the country are represented mainly by the legacy of the First President N. Nazarbayev. The article examines the peculiarities of the creation of these organizations, thei ractivities in providing access to documents and materials, presenting information resources in the global network, as well as participation in corporate international projects for the preservation of cultural and national heritage. The author emphasizes that the cultural and educational activities of the Presidential Library, Museum, Foundation and Archive are aimed not only at the disclosure of their own documentary funds and the popularization of the personality of the founding president, but also at the formation of respect for history and state institutions among young people. The largest institution is the Library of the First President of the Republic of Kazakhstan, which was created in 2014 on the basis of the state institution Nazarbayev Center. And since 2016, the Museum of the First President joined the Library. Therefore, the Library was able to accumulate the most archival, museum, and library resources from the life and activities of the First President of the Republic of Kazakhstan. A feature of the Library of the First President is its interactive nature and the use of the latestinformation and environmental technologies in the building and library processes. And, therefore, accessibility to documentary funds is much higher compared to other similar institutions.